A coupled magneto-thermo-elastic problem in a perfectly conducting elastic half-space with thermal relaxation - S. K. Roy-Choudhuri; Gargi Chatterjee (International Journal of Mathematics and Mathematical Sciences, 1990)
In the present paper we consider the magneto-thermo-elastic wave produced by a thermal shock in a perfectly conducting elastic half-space. Here the Lord-Shulman theory of thermoelasticity [1] is used to account for the interaction between the elastic and thermal fields. The solution obtained in analytical form reduces to those of Kaliski and Nowacki [2] when the coupling between the temperature and strain fields and the relaxation time are neglected. The results also agree with those of Massalas and DaLamangas [3] in absence of the thermal relaxation time.